Is there a wage premium or wage discount for flexible hours? - Miriam Beblo; Anja Heinze; Elke Wolf (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2004)
With flexible work time arrangements firms can quickly adjust to demand fluctuations, while employees may benefit from more time sovereignty. Depending on the specific type of arrangement the accompanying wage effects are ambiguous and have rarely been analyzed. According to the theory of compensating wage differentials, workers with more time sovereignty may be willing to forego earnings whereas others need to be compensated by higher earnings. We analyze the wage effects of work time accounts using GSOEP data from 2002. We compare wages of employees with and without work time accounts by propensity score matching. Our results indicate that work time accountees receive higher wages on average, thus suggesting an employer's discretion to determine the timing of flexible work hours, but with remarkable differences across sectors.
Keywords: J30; 330; work time flexibility; propensity score matching; compensating wage differentials; Lohnstruktur; Arbeitszeitflexibilisierung; Deutschland